Kontribusi kemampuan pemahaman konsep dan rasa percaya diri terhadap hasil belajar matematika siswa kelas X SMK Plus Kemilau Bangsa Batam - Aswandi; Hasibuan, Nailul Himmi; Gusmania, Yesi (Jurnal Pendidik Indonesia, 2020)
Low learning outcomes are indicated due to students' need for more understanding of concepts and their lack of self-confidence. The study aims to determine the combined contribution of the ability to comprehend concepts and self-confidence to the mathematics learning outcomes of 10th-grade students at SMK Plus Kemilau Bangsa Batam. The research design is correlational. The study population consists of a total of 82 students in the 10th grade at SMK Plus Kemilau Bangsa Batam. The sample for this study was taken using simple random sampling technique with the Slovin formula, resulting in 68 students. The instruments used were an essay test consisting of 8 questions and a questionnaire with 30 statements that have been validated and tested for reliability. The data analysis techniques employed were simple linear regression and multiple linear regression. The research findings indicate: (1) the ability to comprehend concepts contributes to mathematics learning outcomes with a coefficient of determination of 9.5%. (2) There is a contribution of self-confidence to mathematics learning outcomes with a coefficient of determination of 8.5%. (3) There is a combined contribution of the ability to comprehend concepts and self-confidence to mathematics learning outcomes with a coefficient of determination of 14.5%, and the regression equation is Y = 3.318 + 0.397X1 + 0.246X2.